Valley of the dolls - Susann, Jacqueline 1918-1974; Williams, John 1932- (<<The>> Criterion Collection, 2016)
"Filmversion von Jacqueline Susanns meistverkauftem Roman, der den Aufstieg und Fall von drei jungen Frauen im Showbusiness dokumentiert." [imdb.com]
Original: USA 1967
two-DVD special edition features: new 2K digital restoration ; audio commentary from 2006 featuring actor Barbara Parkins and journalist Ted Casablanca ; new interviews with writer Amy Fine Collins about author Jacqueline Susann and the costumes in the film ; new video essay by critic Kim Morgan ; footage from "Sparkle Patty sparkle!", a 2009 gala tribute to actor Patty Duke at the Castro Theatre in San Francisco ; "A world premiere voyage" and "Jacqueline Susann and 'Valley of the dolls'", two promotional films from 1967 ; episode of the television program "Hollywood Backstories" from 2001 on the film ; screen tests ; trailers ; plus: a booklet featuring an essay by film critic Glenn Kenny
Bildformat 2.40:1
Keywords: Film; DVD-Video